Indoor Environmental Quality Evaluation Strategy as an Upgrade (Renovation) Measure in a Historic Building Located in the Mediterranean Zone (Athens, Greece) - Chrysanthi Efthymiou (MDPI AG, 2021)
The assessment of indoor environmental quality in historic buildings converted to museums is a significant tool in deep energy renovation processes, as it provides insights for the microclimatic conditions in the interiors of the building where vast numbers of visitors walk every year and where artifacts that are vulnerable to pollution are exhibited. In this work, aiming to contribute to the development of an energy retrofitting protocol applied in the Mediterranean region (HAPPEN MedZeb protocol) for museums hosted in historic buildings by providing useful data, an experimental campaign to evaluate the indoor environmental quality of a museum housed in a historic building located in Athens took place from February 2019 to April 2021 and was divided into two periods. The findings revealed high concentrations of volatile organic compounds as well as poor thermal comfort levels since the sensors recorded low acceptable percentages of T values within the limits from 7 to 33% for the entire experimental period. Based on the findings, recommendations for retrofitting interventions are made.